Pseudomonas aeruginosa in wound infections: Genomic characterization and emergence of hypervirulent ST1965/ST3418 strains co-harbouring exoU and exoS - Xin Hong; Zexuan Li; Wenying Xia; Zhongming Tan; Yulin Hu; Litao Zhang; Genyan Liu (Journal of Global Antimicrobial Resistance, 2025)
Objective: To investigate the phenotype and genotype characteristics of Pseudomonas aeruginosa isolates from wound infections. Methods: Seventy-six P. aeruginosa strains isolated from wound infections in a university hospital were analysed. Antimicrobial susceptibility testing, biofilm formation assays, and whole-genome sequencing were performed on all strains. The virulence of potential hypervirulent strains was assessed using a Galleria mellonella infection model. Results: Among the 76 tested strains, 49 (64.5%) were susceptible to all tested antibiotics. The β-lactamase-encoding gene positivity rate was 57.9%, while the OprD gene mutation rate was 1.3%. All isolates were classified into 56 distinct multilocus sequence types. Serotype distribution revealed O11 (22.37%, 17/76), O16 (19.74%, 15/76), and O1 (18.42%, 14/76) as the most prevalent. The exoU gene was predominantly associated with serotype O11. Over 80% of strains harboured biofilm-related virulence genes, and all exhibited strong biofilm-forming capacity. Six exoU+/exoS+ strains (serotype O4) were identified, with ST1965 and ST3418 demonstrating potential hypervirulence in the infection model. Conclusions: P. aeruginosa isolates from wound infections displayed sporadic genomic profiles, high antibiotic susceptibility, and robust biofilm formation. The emergence of exoU+/exoS+ hypervirulent clones (ST1965 and ST3418), characterized by enhanced virulence and biofilm production, highlights their potential to cause treatment-refractory infections and severe clinical outcomes. Continuous surveillance and tailored therapeutic approaches are imperative for managing infections caused by these clones.